The median effective dose of propofol combined with butorphanol during artificial abortion: a randomized controlled trial - Zheng, Yuling; Huang, Jinping; Mai, Ying; Li, Xiaoling; Zhang, Zhongqi (Frontiers in Medicine, 2023)
Objective Propofol-opioids are the most common drug combination and can reduce the dose of propofol and the incidence of adverse events in painless artificial abortion. We hypothesized that butorphanol may reduce the median effective dose (ED50) of propofol, propofol injection pain, and postoperative uterine contraction pain. Methods This was a randomized, double-blind, controlled study. A total of 54 female patients, who had ASA I or II, aged 18–49 years, undergoing painless artificial abortion, were randomly assigned into two groups, namely, Group P (propofol) and Group PB (propofol plus 10 μg/kg butorphanol). According to the pre-experiment, the initial dose of propofol for the P and PB groups was 3 and 2.5 mg/kg, respectively, with a dose gradient of 0.25 mg/kg. The ED50 of propofol was analyzed using probit regression analysis. The total propofol dose consumed, recovery time, and anesthesia-related adverse events were also recorded. Results There were 25 and 29 patients in the P and PB groups, respectively. The ED50 (95% CI) of propofol for artificial abortion were 2.477 (2.186–2.737) and 1.555 (1.173–1.846) mg/kg in the P and PB groups, respectively. The total propofol dose consumed was (150.7 ± 21.7) mg and (110.4 ± 28.2) mg in the P and PB groups, respectively (P < 0.001). Compared with the P group, injection-site pain (76 vs. 20.7%) and uterine contraction pain (72 vs. 6.9%) in the PB group had a significant decrease (P < 0.001). Conclusion Combination of propofol with 10 μg/kg butorphanol reduced the ED50 of propofol and decreased the incidence of propofol injection-site pain and postoperative uterine contraction pain during painless artificial abortion compared with propofol alone. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=166610, identifier: ChiCTR2200059795.